Use of e-Cigarettes and Development of Respiratory Conditions in Women of Childbearing Age. Issue 10 (October 2020) - Parekh, Tarang; Owens, Constance; Fay, Kathryn; Phillips, Joseph; Kitsantas, Panagiota
Abstract : Objective: Women of childbearing age are encouraged not to smoke because of well-documented adverse health outcomes. This study examines the association between e-cigarette use and respiratory conditions (asthma and chronic obstructive pulmonary disease [COPD]) among women of childbearing age. Methods: The study used data from the Behavioral Risk Factor Surveillance System 2016–2017. The sample consisted of 131, 965 women of childbearing age (18–44 years old). The main independent variable was smoking status and the primary outcomes were self-reported respiratory conditions such as asthma and COPD. Data were analyzed using descriptive statistics and multivariate logistic regression to assess the effects of e-cigarettes on asthma and COPD. Results: In this sample of childbearing-age women, 2.79% were current e-cigarettes users with or without a history of combustible cigarette smoking and 3.02% were current dual users. Compared with nonsmokers, current e-cigarette users without a history of combustible cigarette smoking were associated with 74% higher odds of having asthma (adjusted odds ratio [AOR] 1.74, 95% confidence interval [CI] 1.29–2.35), whereas results were not significant for COPD. The odds of having COPD, however, were 3 times higher (AOR 3.28, 95% CI 2.62–4.12) for current e-cigarette users with a history of cigarette smoking, whereas current dual users showed 5 times higher odds (AOR 5.07, 95% CI 3.91–6.56) of COPD compared with nonsmokers. Conclusion: Policies related to e-cigarettes need to be reevaluated and clearly communicated to improve prevention efforts for women of childbearing age. Abstract : Many young women of childbearing age are using e-cigarettes as an alternative to smoking, which could affect pregnancy outcomes. This study examines the association between e-cigarette use and smoking status of women of childbearing age and respiratory conditions, mainly asthma and chronic obstructive pulmonary disease.